2010
DOI: 10.1111/j.1439-0426.2010.01418.x
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of skeletons and intervertebral disks in live fish larvae by fluorescent calcein staining and disk specific GFP expression

Abstract: Zebrafish and medaka have become popular models for studying skeletal development because of high fecundity, shorter generation period, and transparency of fish embryo. The first step to study skeletal development is visualizing bone and cartilage. Live animal staining with fluorescent calcein have several advantages over the standard skeletal staining protocol by using alizarin red and alcian blue for bone and cartilage. However, there is no detailed study examining skeletal development of live marine fish la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…We used in vivo calcein staining, marking osteoblasts, and bone in live zebrafish (Du et al, 2001; Haga et al, 2010), to determine whether TCDD exposure inhibits ossification of the jaw cartilages. In control zebrafish embryos at 144 hpf, we found clear calcein staining in ceratohyal, dentary, and quadrate bone in whole mount live fluorescent images (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used in vivo calcein staining, marking osteoblasts, and bone in live zebrafish (Du et al, 2001; Haga et al, 2010), to determine whether TCDD exposure inhibits ossification of the jaw cartilages. In control zebrafish embryos at 144 hpf, we found clear calcein staining in ceratohyal, dentary, and quadrate bone in whole mount live fluorescent images (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because the notochord was present at fused centra at 53 dpf and had been degenerated at 121 dpf, it is hypothesized that the notochord gradually degenerates during larval to adult growth after fusion of centra. In zebrafish, it was also reported that RA exposure causes degeneration of notochord (Haga et al, 2010). Considering that the notochord cells produce extracellular matrices that form notochord sheath essential for intervertebral joint formation (Kaneko et al, 2016), it is presumed that degeneration of the notochord accelerates the progress of vertebral deformity.…”
Section: Discussionmentioning
confidence: 99%
“…Fin rays were then fixed overnight in 10% buffered formalin, stepped into a 0.3% KOH solution, and mixed with 1–2 drops of 30% hydrogen peroxide per 100 ml of solution to remove skin pigmentation. Fin rays were then stained in calcein solution ( N = 2 for each species) following published methods (Haga et al, ) or cleared and stained ( N = 2 for each species) with alizarin red following published methods (Dingerkus & Uhler, ; Potthoff, ). Each fin ray's medio‐lateral surface was photographed under fluorescent light to aid in the visualization of segmentation.…”
Section: Methodsmentioning
confidence: 99%
“…Fin rays were then stained in calcein solution (N 5 2 for each species) following published methods (Haga et al, 2010) or cleared and stained (N 5 2 for each species) with alizarin red following published methods (Dingerkus & Uhler, 1977;Potthoff, 1984). Each fin ray's medio-lateral surface was photographed under fluorescent light to aid in the visualization of segmentation.…”
Section: Fin Ray Morphologymentioning
confidence: 99%